VD_FINDINFO AI 19/12 - 151/2012 vom 24. April 2012 - VD Tribunal cantonal (2012)
DÉCISION DE RENVOI, MESURE D'INSTRUCTIONASSURANCE SOCIALE, EXPERTISE PLURIDISCIPLINAIRE | 57 al. 1 let. f LAI, 43 LPGA, 44 LPGA, 69 RAI, 82 LPA-VD